Erectile dysfunction (ED) after ischemic stroke: association between prevalence and site of lesion - Koehn, Julia; Crodel, Carl; Deutsch, Martina; Kolominsky-Rabas, Peter; Hoesl, Katharina M.; Köhrmann, Martin; Schwab, Stefan; Hilz, Max-Josef (Clinical Autonomic Research, 2015)
Stroke may cause or worsen erectile dysfunction (ED). Post-stroke ED prevalence and association with stroke location are not well established. Therefore, we assessed post-stroke ED prevalence in relation to ischemic lesion locations and stroke severity.In 57 men (62.6 ± 10.5 years) who had ischemic stroke within 24 months prior to evaluation, we used the five-item International Index of Erectile Function questionnaire (IIEF5) to evaluate ED prevalence after stroke and retrospectively 3 months prior to stroke. IIEF5 scores range from 5 to 25; scores below 22 indicate ED. We estimated stroke severity upon hospital admission, using the National Institute of Health Stroke Scale (NIHSS), and determined stroke location from cranial computed tomography or magnetic resonance imaging. We compared pre- and post-stroke results with those of 22 control persons (61.7 ± 11.2 years), calculated correlations between IIEF5 scores and NIHSS scores, and compared ED prevalence with stroke locations (significance: p < 0.05).ED was reported by 45/57 patients after stroke, 26/57 patients before stroke, and 6/22 control persons. Patients' IIEF5 values were significantly lower [median 16 interquartile range (IQR) 3.5-20.5] after than before stroke (median 23, IQR 19.0-24.0) and lower than in controls (median 24, IQR 19.8-25.0). Pre- and post-stroke IIEF5 scores did not correlate with the patients' NIHSS scores at stroke onset (p > 0.05). ED was associated with middle cerebral artery infarction in 27/34, posterior cerebral artery infarction in 4/5, anterior cerebral artery infarction in 1/1, basal ganglia infarction in 3/3, brain stem infarction in 8/10, cerebellar infarction in 2/5, and lesions in more than one region in 1/1 patients.Disruption of the central network assuring erection might contribute to increased ED severity and prevalence after stroke. Anti-erectile effects of functional and psychological impairment or medication added after stroke may also contribute to ED but must be evaluated in larger patients groups.
EVALuna2:22368